Association between systemic lupus erythematosus and insertion/deletion polymorphism of the angiotensin converting enzyme (ace) gene - PULLMANN, R. JR; LUKAC, J; SKERENOVA, M; ROVENSKY, J; HYBENOVA, J; MELUS, V; CELEC, S; HYRDEL, R (Clinical and experimental rheumatology, 1999)
ACE takes part in the renin-angiotensin and kallikrein-kininogen systems by creating angiotensin-II and inactivating bradykinin. ACE gene insertion/deletion polymorphism is associated with the level of circulating enzymes--subjects with the DD genotype have higher levels of circulating ACE than subjects with the II genotype and show an increased tendency towards impaired vascular function and structure. Patients with systemic lupus erythematosus (SLE) suffer from differentially expressed vascular pathology. We attempted to determine whether the type of ACE polymorphism could contribute to this pathology. 101 SLE patients fulfilling the ACR criteria were investigated. The I/D polymorphism was ascertained by PCR, followed by electrophoresis of the amplified fragments and UV visualization. The frequency of the D allele was higher in the SLE group (0.623) than in the controls (0.520) (chi 2 test, p < 0.025). The distribution of the ACE genotype in SLE group was different from that in the control group (p < 0.05). An association between the DD genotype and visceral damage (p < 0.006) was observed. Our results suggest that in the multifactorially determined vascular pathology of SLE, changes associated with I/D polymorphism could influence vessel wall inflammation (monocyte adhesion and activation with cytokine release, T-lymphocyte metabolism), a tendency towards vascular impairment (neointimal proliferation, vasospasm, platelet activation, myocyte proliferation) and lead to the subsequent ischemia. The ACE gene could serve as the visceral damage indicator in SLE.